The Africa Food Environment Research Network (FERN): from concept to practice. (June 2023) - Tandoh, Akua; Aryeetey, Richmond; Agyemang, Charles; Holdsworth, Michelle; Asiki, Gershim; Zotor, Francis; Mensah, Kobby; Laar, Matilda E.; Laryea, Dennis; Sellen, Daniel; Vandevijvere, Stefanie; Laar, Amos
Background: Africa is contending with unhealthy food environments that are, in part, driving increasing rates of overweight, obesity and diet-related non-communicable diseases, alongside persistent undernutrition. This current paradigm requires expanded efforts – both in the volume and nature of empirical research, as well as the tools and capacity of those who conduct it. High quality and context-relevant research supports the development and implementation of policies that create healthy food environments. Aim and approach: This paper sets out the concept of the Africa Food Environment Research Network (FERN) initiative recently established by the Measurement, Evaluation, Accountability, and Leadership Support for non-communicable diseases (NCDs) (MEALS4NCDs) prevention project. Central to the Africa FERN initiative are: 1) building research capacity for innovative food environment research in Africa; 2) improving South–South, South–North partnerships to stimulate robust food environment research and monitoring in Africa and 3) sustaining dialogue and focusing priorities around current and future needs for enhanced food environment research and monitoring in Africa. Conclusion: The FERN initiative presents an opportune platform for researchers in Africa and the global North to weave the threads of experience and expertise for research capacity building, collaboration and advocacy, to advance food environment research.